Sarcoglycanopathy - A Rare Case Report and Literature Review - Mustafa, Ekramul; Khandaker, Md. Azizul Hasan; Rashid, Md. Mamunur; Ghose, Swapon Kumar; Chowdhury, Mostofa Kamal (Journal of Medicine, 2014)
<!–[if gte mso 9]> <![endif]–> Sarcoglycanopathies are relatively rare progressive muscular dystrophies with autosomal recessive inheritance designated as a, b, g, or d sarcoglycanopath.; which belong to the group of limb girdle muscular dystrophies (LGMD) and are caused by mutations in any of the four sarcoglycan genes: alpha (LGMD 2D), beta (LGMD 2E), gamma (LGMD 2C) and delta (LGMD 2F). The phenotype resembles dystrophinopathies due to proximal muscle weakness and calf hypertrophy. Reports from Bangladesh are scarce. We report a rare case of primary sarcoglycanopathy (SGP) which emphasizes the evolving concept of dystrophinopathy to sarco-glycanopathy and describe literature pertaining to this rare entity. DOI: http://dx.doi.org/10.3329/jom.v15i1.19880 J Medicine 2014; 15: 77-79 <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE BN <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>